Sources of all-trans retinal oxidation independent of the aldehyde dehydrogenase 1A isozymes exist in the postnatal testis. Issue 2 (21st September 2018) - Beedle, My-Thanh; Stevison, Faith; Zhong, Guo; Topping, Traci; Hogarth, Cathryn; Isoherranen, Nina; Griswold, Michael D
Abstract: Despite the essential role of the active metabolite of vitamin A, all-trans retinoic acid ( at RA) in spermatogenesis, the enzymes, and cellular populations responsible for its synthesis in the postnatal testis remain largely unknown. The aldehyde dehydrogenase 1A (ALDH1A) family of enzymes residing within Sertoli cells is responsible for the synthesis of at RA, driving the first round of spermatogenesis. Those studies also revealed that the at RA required to drive subsequent rounds of spermatogenesis is possibly derived from the ALDH1A enzymes residing within the meiotic and post-meiotic germ cells. Three ALDH1A isozymes (ALDH1A1, ALDH1A2, and ALDH1A3) are present in the testis. Although, ALDH1A1 is expressed in adult Sertoli cells and is suggested to contribute to the at RA required for the pre-meiotic transitions, ALDH1A2 is proposed to be the essential isomer involved in testicular at RA biosynthesis. In this report, we first examine the requirement for ALDH1A2 via the generation and analysis of a conditional Aldh1a2 germ cell knockout and a tamoxifen-induced Aldh1a2 knockout model. We then utilized the pan-ALDH1A inhibitor (WIN 18446) to test the collective contribution of the ALDH1A enzymes to at RA biosynthesis following the first round of spermatogenesis. Collectively, our data provide the first in vivo evidence demonstrating that animals severely deficient in ALDH1A2 postnatally proceed normally through spermatogenesis. Our studies with a pan-ALDH1A inhibitor (WIN 18446) also suggest that an alternative source of at RA biosynthesis independent of the ALDH1A enzymes becomes available to maintain at RA levels for several spermatogenic cycles following an initial at RA injection. Abstract : Elimination of ALDH1A enzymatic activity following a single pulse of retinoic acid does not immediately ablate spermatogenesis due to the presence of an additional source of at Retinal oxidation.